How Urban Identity, Affect, and Knowledge Predict Perceptions About Coyotes and Their Management. (2nd January 2020) - Drake, Michael D.; Nils Peterson, M.; Griffith, Emily H.; Olfenbuttel, Colleen; DePerno, Cristopher S.; Moorman, Christopher E.
ABSTRACT: Globally, the number of humans and wildlife species sharing urban spaces continues to grow. As these populations grow, so too does the frequency of human–wildlife interactions in urban areas. Carnivores in particular pose urban wildlife conservation challenges owing to the strong emotions they elicit and the potential threats they can present to humans. These challenges can be better addressed with an understanding of the different factors that influence public perceptions of carnivores and their management. We conducted mail surveys in four cities in North Carolina ( n =721) to explore how (a) city of residence, (b) affectual connections to coyotes ( Canis latrans ), and (c) biological knowledge predicted perceptions of the danger posed by coyotes, the support for wild coyotes living nearby, and the support for lethal coyote removal methods. Our results provide the first assessment of how public perceptions of carnivores and their management vary between cities of different types. Residents from a tourism-driven city were more supportive of coyotes than residents from an industrial city and less concerned about risk than residents from a commercial city. We found affectual connection to coyotes and city of residence were consistent predictors of coyote perceptions. Respondents' knowledge of coyote biology was not a significant predictor of any perceptions of coyotes despite the relatively high statistical power of the tests. Affectual connection to coyotes had the greatest effect on predicting coyote perceptions, suggesting efforts to promote positive emotional connections to wildlife may be a better way to increase acceptance of carnivores in urban areas than focusing on biological knowledge.